Development of a flexible pressure sensor for measurement of endotension - Isa C. T. Santos (2010)
An aneurysm is a bulge in a weakened portion of a blood vessel wall much like the bulge that results from over-inflating an inner tube. If left untreated, it may burst or rupture causing shock and/or death due to massive blood loss. Endovascular aneurysm repair (EVAR) is one of the treatments available for aortic aneurysms but, in spite of major advances in the operating techniques, complications still occur and lifelong surveillance is recommended. Current surveillance protocols are based on medical imaging exams that besides being expensive are time consuming. After a brief introduction to EVAR and its complications, this paper reviews post-EVAR surveillance protocols and the current devices to measure endotension. Finally, are introduced two new concepts for a flexible pressure sensor with passive telemetry.